2019
DOI: 10.21122/1029-7448-2019-62-2-377-387
|View full text |Cite
|
Sign up to set email alerts
|

Modern Methods of Urban Energy System Planning

Abstract: Knowledge of the nature of the energy load alterations not only in time, but also in space will allow achieving the optimal structure of energy sources in the city and thereby reducing unproductive energy costs of energy resources and increasing energy efficiency. Changing the paradigm of power supply systems development towards the development of small distributed power production, intellectualization and demand management requires a more accurate understanding of the planned local loads in the city. At prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Before the 2020 crisis the issues of energy development were considered by Russian economists from various perspectives: from a popular problem of spreading renewable sources of energy to the general questions of developing the energy complex, including on the territory of the Arctic zone [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Before the 2020 crisis the issues of energy development were considered by Russian economists from various perspectives: from a popular problem of spreading renewable sources of energy to the general questions of developing the energy complex, including on the territory of the Arctic zone [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Based on the international experience [2][3][4][5][6][7][8][9][10] and synthesis of different instruments the extrapolation modelling of electrical energy generation and selling with the help of innovative technologies was done. The analysis of the current technologies and best practices allowed to find the optimal way to implement innovative technologies in the power supply market in Russian Federation.…”
Section: Methodsmentioning
confidence: 99%
“…Energies 2022, 15, 1015 2 of 14 Obviously, the issues of ensuring sustainable development in the heat supply industry that require research, are concentrated to the greatest extent where their growth was observed even in the "pre-pandemic" period. Of course, the forecast of energy consumption is also important, which determines the possibilities within which realistic tasks of planning the development of the energy supply system will be set [1].…”
Section: Introductionmentioning
confidence: 99%